Health literacy and its predictors among urban and rural adults in Bijar County - Bahman Baraie; Tahereh Pashaei; Edris Kakemam; Hassan Mahmoodi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND PURPOSE: The World Health Organization has identified health literacy (HL) as one of the most important determinants of people's health. Therefore, this research aimed to investigate the status of HL and its predictors. MATERIALS AND METHODS: This research was a cross-sectional study that was performed on 600 adults in Bijar County, Iran. Cluster sampling was used to select the samples. Data were collected using the questionnaire of HL for Iranian adults. Data were analyzed using one-way analysis of variance, Student's t-test, and multiple linear regression in SPSS 21. RESULTS: The mean score of HL was 3.6 out of 5; 69% and 29% of the samples had a moderate-to-high health status, respectively. Among the dimensions of HL, the highest and the lowest means were perception (3.94) and evaluation (3.21), respectively. Based on the multiple regression results, the variables (gender - B = −0.142, confidence interval [CI]: −0.409 to −0.011, P = 0.39; education level - B = 0.391, CI: 0.149-0.287, P = 0.00; and income level - B = 0.203, CI: 0.00-0.00, P = 0.01) were significantly positively associated with HL. CONCLUSION: The results of this study can be applied to educational interventions through media and radio-television to increase public awareness. Education is also strongly recommended in terms of demographic variables and characteristics to promote HL in the society.